Value Promise versus Value Delivery. (May 2015) - Rao, Ajit
This article is about the inevitability for organizations to move away from offering 'commodity' customer service to an 'on brand' customer service. This article focuses on the need for organizations to align the promises that they are making while communicating the benefits of their brand with their current and potential customers, with the actual delivery of that promise. The benefits of such an alignment will result in stronger brand equity, greater customer centricity, increased levels of loyalty and concrete differentiation in the marketplace. The article begins with a review of the current situation of 'on brand' service gauging some of the reasons as to why delivery is not aligned with the promises made by the brand, and showcases some success stories. The article then discusses a tool that provides organizations with the ability to translate the brand promise into service delivery at every customer interaction resulting in authentic and memorable 'moments-of-truth' for the customer. This article is based on the author's experiences, observations, empirical evidence, and formal and informal discussions with his clients and non-clients.